2010
DOI: 10.1177/0022022110383424
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Latino Adolescents’ Perceptions of Discrimination, Neighborhood Risk, and Parenting on Self-Esteem and Depressive Symptoms

Abstract: Guided by Bronfenbrenner’s bioecological framework, this study examined the roles of Latino adolescents’ reports of discrimination, neighborhood risk, parent-child conflict over culture, and parental support in relation to their self-esteem and depression. Analysis of self-report data from 383 ninth grade, Latino students from one Los Angeles high school was used to validate a Multigroup Structural Equation Model of self-esteem and depressive symptoms for boys and girls. As expected, self-esteem was negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 91 publications
10
105
0
2
Order By: Relevance
“…Furthermore, while males tend to be at greater risk for many of the negative developmental consequences of racism and discrimination, females' self-esteem appears to be at the greatest risk in the face of perceived discrimination (Behnke, Plunkett, Sands, & Bámaca-Colbert, 2011;Umaña-Taylor & Updegraff, 2006). As perceptions of societal discrimination increase, global self-esteem tends to decrease (Behnke et al, 2011). Notably, for females this decrease is much more pronounced-it is steep, and occurs more rapidly than it does for males (Umaña-Taylor & Updegraff, 2006).…”
Section: Self-esteemmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, while males tend to be at greater risk for many of the negative developmental consequences of racism and discrimination, females' self-esteem appears to be at the greatest risk in the face of perceived discrimination (Behnke, Plunkett, Sands, & Bámaca-Colbert, 2011;Umaña-Taylor & Updegraff, 2006). As perceptions of societal discrimination increase, global self-esteem tends to decrease (Behnke et al, 2011). Notably, for females this decrease is much more pronounced-it is steep, and occurs more rapidly than it does for males (Umaña-Taylor & Updegraff, 2006).…”
Section: Self-esteemmentioning
confidence: 98%
“…It has been demonstrated repeatedly that the development of strong ethnic identity is essential for both adolescent and adult well-being; however, solid ethnic identity cannot be built on a shaky foundation of weakened self-esteem. Furthermore, while males tend to be at greater risk for many of the negative developmental consequences of racism and discrimination, females' self-esteem appears to be at the greatest risk in the face of perceived discrimination (Behnke, Plunkett, Sands, & Bámaca-Colbert, 2011;Umaña-Taylor & Updegraff, 2006). As perceptions of societal discrimination increase, global self-esteem tends to decrease (Behnke et al, 2011).…”
Section: Self-esteemmentioning
confidence: 99%
See 1 more Smart Citation
“…They were also able to detect how different kinds of accumulated risks (emanating from the micro, meso or exo level or individual factors) were associated with different behavioural problems (aggressive behaviour versus anxiety and depression). Likewise, Behnke et al (2011) were able to detect how the association between factors at different ecological levels and depressive symptoms differed for girls and boys. Equally, Romano et al (2015), in their review of the complex relationship between childhood maltreatment and later academic achievement and mental health, found that the negative consequences of childhood maltreatment seemed to be greater for boys than girls.…”
Section: Studies Utilizing Ecological Systems Concepts By Consideringmentioning
confidence: 99%
“…Observational studies that examined sub-sets of the population (k = 9) included the following: children from politically violent areas in the Gaza Strip and West Bank (Al-Krenawi and Graham, 2012), children of Latin American background (Behnke et al, 2010), children of mothers exposed to partner violence (Kennedy et al, 2010), child soldiers of war (Kohrt et al, 2010); children of African American background (Lambert et al, 2010;Simons et al, 2002), children of African American background who are at risk of or have been abused (Lindsey et al, 2008), children from Hispanic and African American backgrounds (Rosario et al, 2008) (Ialongo et al, 1999); BPI: Behaviour Problems Index (Zill, 1985); BSI: Brief Symptom Inventory (Derogatis and Melisaratos, 1983); C: Children's reports; CAPA: Child and Adolescent Psychiatric Assessment ; CBCL: Child Behaviour Checklist (Achenbach, 1991); CDI: Child Depression Inventory (Kovacs, 1984); CES-D: Center for Epidemiologic Studies Depression Scale (Radloff, 1977); CI: Confidence Interval; DAWBA: Development and Well-being Assessment (Goodman and Ford, 2000); DSRS: Depression Self Rating Scale (Birleson et al, 1987); DISC: Diagnostic Interview Schedule for Children (Shaffer et al, 1993) and children from low-socio-economic backgrounds (Witherspoon et al, 2009). Details of participants in studies examining community interventions are provided in Table 4.…”
Section: Participantsmentioning
confidence: 99%